The effectiveness of blended learning continuing education program on toxoplasmosis for basic education teachers (Research, Society and Development, 2021)
Toxoplasmosis is a zoonosis of great importance for public health since it is referenced as causing changes in human fetuses and animals. This research aims at comparing the knowledge of 165 basic education professionals before and after a blended learning online course (180-hour) on toxoplasmosis. A health education course on major urban zoonoses was offered once a year between 2009 and 2013 on the Virtual Learning Environment TelEduc platform. An open question questionnaire on Toxoplasmosis was applied before and after the specific module, and the responses were categorized according to the literature review theme. The initial and final evaluations addressed issues such as toxoplasmosis etiologic agent, clinical signs in animals and humans, and form of transmission and prevention. Toxoplasmosis general knowledge increased significantly (p